ANALISIS FAKTOR KUALITAS PELAYANAN UPA PERPUSTAKAAN UNIVERSITAS HALU OLEO DENGAN METODE SEM-LISREL - Mohammad Ricky Ramadhan Rasyid (Program Studi Ilmu Komputer FMIPA-UHO, 2025)
This study aims to analyze the factors influencing service quality at the Library of Halu Oleo University by employing the Structural Equation Modeling (SEM) method supported by LISREL 8.80 software. The variables examined include service quality (X1) and library facilities (X2) as exogenous variables, as well as perceived quality (Y) as the endogenous variable. Data were collected through questionnaires distributed to 100 library users from various faculties and academic years who visited the library. Each indicator was measured using a five-point Likert scale. The data were analyzed through several stages, including tests of normality, validity, reliability, measurement model estimation, and structural model evaluation. The results of the validity and reliability tests showed that the indicators used met the required criteria for loading factor, t-value, Construct Reliability (CR), and Variance Extracted (VE). The structural model analysis revealed that service quality had a positive and significant effect on perceived quality, with a coefficient of 0.78. Meanwhile, library facilities also had a positive and significant effect, with a coefficient of 0.29. The R² value of 0.89 indicates that 89% of the variance in perceived quality can be explained by these two variables. This study demonstrates that service quality plays the most dominant role in enhancing users’ perceptions of library service quality, followed by library facilities. These findings emphasize the importance of improving service performance and managing library facilities effectively to create an optimal service experience for users